Materiales didácticos y su incidencia en el desarrollo de la motricidad gruesa en estudiantes de inicial de la Unidad Educativa "Francisco Huerta Rendón" cantón Babahoyo - Coello Zambrano, Tatiana Estefanía (2023)
Gross motor skills in preschool students (0 to 5 years old) is an essential aspect in their learning process, they are skills that involve the large muscles of the body, such as crawling, walking, running, jumping. These are fundamental for the physical and cognitive development of infants, because they allow them to explore their environment, acquire new knowledge and interact with others. However, it is important to emphasize that the development of gross motor skills not only depends on the genetics and the physical environment in which the student develops, but also on the quality of the didactic materials that are used to promote this development. In many preschool educational institutions, the teaching materials used for gross motor development are insufficient or inadequate. In some cases, the materials are outdated or in poor condition, making them difficult to use and limiting learning possibilities. In other cases, the materials are not designed to encourage gross motor development, but focus on other areas of learning. This has become a problem, as it has been proven that the use of appropriate and appropriate teaching materials can significantly improve the development of gross motor skills in preschool students.